Pengaruh Keselamatan dan Kesehatan Kerja Terhadap Produktivitas Kerja Melalui Disiplin Kerja Sebagai Variabel Intervening pada PT X - Rizka Putri Amelia; Tangguh Dwi Pranomo (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
Employee work productivity is one of the main indicators in achieving organizational goals. Among the various factors that affect work productivity, Occupational Safety and Health (OHS) and work discipline play an important role. This study aims to determine the effect of OHS on employee work productivity with work discipline as a mediating variable at the Main Office of PT X. The scope of this study is limited to the analysis of the impact of OHS on work productivity through the mediating influence of work discipline. The research method used is quantitative descriptive, which provides a comprehensive picture of the phenomenon by collecting numerical and statistical data. The sampling technique used is total sampling (next to saturated), involving all 96 employees as respondents. Data collection was carried out using a structured questionnaire via Google Forms, and analyzed using SmartPLS 3.0 software through the Structural Equation Modeling (SEM) approach. This study shows that Occupational Safety and Health has a positive and significant effect on work discipline. Work Discipline has a positive and significant effect on work productivity. has a role as a mediator in the influence of Occupational Safety and Health on work productivity with a partial mediation category.